An eco-friendly tandem tosylation/Ferrier N-glycosylation of amines catalyzed by Er(OTf)3 in 2-MeTHF. Issue 18 (3rd May 2017) - Nardi, Monica; Cano, Natividad Herrera; De Nino, Antonio; Di Gioia, Maria Luisa; Maiuolo, Loredana; Oliverio, Manuela; Santiago, Ana; Sorrentino, Diletta; Procopio, Antonio
Graphical abstract: Highlights: Convenient synthesis of sulfonamides and 2, 3-unsaturated- N -pseudoglycals. Green procedure in 2-MeTHF. Application of erbium (III) trifluoromethanesulfonate as a Lewis acid catalyst. Abstract: Er(OTf)3 in 2-MeTHF provides a new and eco-friendly process for Ferrier glycosylation of sulfonamides and amino acids with various N -nucleophiles. The stereoselective synthesis of 2, 3-unsaturated- N -pseudoglycals was carried out with 3, 4, 6-tri-O-acetyl-d -glucal and different nucleophiles affording good results in a short time.